Down-Regulating the Expression of miRNA-21 Inhibits the Glucose Metabolism of A549/DDP Cells and Promotes Cell Death Through the PI3K/AKT/mTOR/HIF-1α Pathway - Sun, Ye; Liu, Wenjun; Zhao, Qiuyu; Zhang, Ruiqi; Wang, Jianbo; Pan, Pengyu; Shang, Hai; Liu, Chunying; Wang, Chun (Frontiers in Oncology, 2021)
miRNA-21 is a single-stranded non-coding RNA that is highly expressed in a variety of tumor cells. It participates in tumor cell proliferation, metabolism, metastasis, and drug resistance. Here, we tested the potential mechanism of miRNA-21 in cisplatin-resistant non-small cell lung cancer A549/DDP (human lung adenocarcinoma drug-resistant cell line) cells. A549 and A549/DDP RNAs were sequenced to show that miRNA-21 was highly expressed in the latter, and this was verified by qRT-PCR. In addition, we found that miRNA-21 combined with cisplatin can significantly inhibit glycolysis and glycolysis rate-limiting enzyme protein expression in A549/DDP cells. We also found that miRNA-21 combined with cisplatin can promote A549/DDP cell death. Further investigations showed that miRNA-21 combined with cisplatin caused excessive inactivation of the pI3K/AKT/mTOR/HIF-1 signaling pathway in cisplatin-resistant A549/DDP cells. Hence, reduction of the expression of miRNA-21 in combination with cisplatin chemotherapy may effectively improve the therapeutic effect on patients with non-small cell lung cancer, and this may provide a theoretical basis for the treatment of this disease.